2020
DOI: 10.1177/0269215520980138
|View full text |Cite
|
Sign up to set email alerts
|

A six-week inspiratory muscle training and aerobic exercise improves respiratory muscle strength and exercise capacity in lung cancer patients after video-assisted thoracoscopic surgery: A randomized controlled trial

Abstract: Objective: To compare the postoperative outcomes of inspiratory muscle training and aerobic exercise, along with standard care, on lung cancer patients undergoing video-assisted thoracoscopic surgery (VATS). Design: A parallel-group, single-blind randomized clinical trial Setting: Thoracic surgery ward and outpatient clinic in a teaching hospital Subjects: Overall 63 patients underwent VATS were randomly assigned to a triaging (TG, n = 32) or control group (CG, n = 31). A total of 54 patients (TG, n = 26; CG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 28 publications
0
49
0
Order By: Relevance
“…15,18,19,30,34 Two studies had daily physiotherapy sessions, 16,21 three studies included physical training. 4,14,17…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…15,18,19,30,34 Two studies had daily physiotherapy sessions, 16,21 three studies included physical training. 4,14,17…”
Section: Resultsmentioning
confidence: 99%
“…Four postoperative studies reported the days of needing chest tube (two to five days), and each study found no between-group differences. 15 17,30 Five studies reported data on mortality: one study reported zero mortalities in both groups, 18 two studies reported one death (1.1%–2.9%) in the control group 15,34 one study reported one death in the treatment group (2.4%), 21 and one study reported one death in the intervention group (1.6%) and four in the control group (6.0%). 14 The included perioperative study reported the median and interquartile range of postoperative length of hospital stay and found no between-group differences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations